2005
DOI: 10.1111/j.1651-2227.2005.tb02169.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective 10‐year study on children who had severe infantile colic

Abstract: Aim: To evaluate the association between infantile colic and gastrointestinal, allergic and psychological disorders in childhood. Methods: A prospective study was conducted on 103 infants aged 31–87 d. After 10 y, between 2001 and 2003, the children were recalled and a paediatrician evaluated the selected disorders by anamnesis, medical examination, laboratory tests and parent interviews. Results: Of the 103 infants enrolled, 96 completed the study. There was an association between infantile colic and recurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
2
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(42 citation statements)
references
References 29 publications
2
33
2
5
Order By: Relevance
“…Another longitudinal birth cohort study of 1327 infants links regulatory problems between 2 and 10 months of age with a nearly threefold risk of functional somatic symptoms at school-age [84]. A retrospective study of 1467 children with sensory processing and autistic spectrum disorders found an increased rate of early regulatory problems [85]; a prospective study of 96 infants diagnosed with excessive crying in the first twelve weeks demonstrated an increased incidence of allergy and behavioural problems at ten years of age [86]; and a retrospective study of 208 children older than six years presenting with migraines showed they were more likely to have cried excessively in the first few months of life [87]. Widespread unnecessary medicalization of cry-fuss problems in the first three to four months predisposes to allergy and GORD in later infancy; allergy is associated with poorer neurodevelopmental outcomes [88], and GORD is associated with maternal psychological disturbance and persistent infant feeding problems [89].…”
Section: Discussionmentioning
confidence: 98%
“…Another longitudinal birth cohort study of 1327 infants links regulatory problems between 2 and 10 months of age with a nearly threefold risk of functional somatic symptoms at school-age [84]. A retrospective study of 1467 children with sensory processing and autistic spectrum disorders found an increased rate of early regulatory problems [85]; a prospective study of 96 infants diagnosed with excessive crying in the first twelve weeks demonstrated an increased incidence of allergy and behavioural problems at ten years of age [86]; and a retrospective study of 208 children older than six years presenting with migraines showed they were more likely to have cried excessively in the first few months of life [87]. Widespread unnecessary medicalization of cry-fuss problems in the first three to four months predisposes to allergy and GORD in later infancy; allergy is associated with poorer neurodevelopmental outcomes [88], and GORD is associated with maternal psychological disturbance and persistent infant feeding problems [89].…”
Section: Discussionmentioning
confidence: 98%
“…Notwithstanding, what is clear is that underlying disease is rare in the excessively crying baby 4 and that half of those affected recover by 6 months of age, 5 with a small proportion at risk of injury 6 or long-term developmental problems. [7][8][9] In an effort to help their child with what appears to be a painful condition, some parents choose complementary and alternative medicine (CAM), including chiropractic manual therapy. [9][10][11][12] To date, several randomized trials have been reported, [13][14][15][16][17][18][19] and although these trials demonstrate some reduction in crying, weaknesses in study methodologies have compromised their contribution to the evidence base.…”
mentioning
confidence: 99%
“…16 Some research studies have shown these traits affect the child until he is 8 to 10 years of age. 17 Further rigorous research is required to determine whether chiropractic treatment of infant colic can reduce the longterm effects on other behavior problems for a larger sample as well as for older age groups.…”
Section: Discussionmentioning
confidence: 99%